1952
DOI: 10.1002/jctb.5010021208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phosphate on the constitution and hardening of portland cement

Abstract: The effect of phosphorus pentoxide on the burning of Portland‐cement clinker and the setting and hardening of the resultant cement has been investigated, using both synthetic mixtures and the raw materials which it is proposed to use for cement manufacture in Uganda. It is shown that the P2O5 forms a solid solution with the 2CaO,SiO2 of the cement clinker and reduces the content of 3CaO,SiO2. Consequently the early strength falls as the P2O5 increases until, when the P2O5 reaches 2·25% of the clinker, the ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 2 publications
0
22
0
5
Order By: Relevance
“…The partial replacement of fossil fuel by using MBM as an alternative represents a source of an additional amount of P 2 O 5: This is due to the ability of clinker to incorporate various levels of ash and the phosphorus inorganic compounds present in these materials would combine mainly with the silicates (alite and belite) formed during clinkering. 6,7 It has been shown that a high level of phosphorus inhibits the formation of alite. Halicz and Nathan 8 obtained synthetic clinkers that were prepared from oil shale containing up to 5 wt% P 2 O 5 as a secondary component.…”
mentioning
confidence: 99%
“…The partial replacement of fossil fuel by using MBM as an alternative represents a source of an additional amount of P 2 O 5: This is due to the ability of clinker to incorporate various levels of ash and the phosphorus inorganic compounds present in these materials would combine mainly with the silicates (alite and belite) formed during clinkering. 6,7 It has been shown that a high level of phosphorus inhibits the formation of alite. Halicz and Nathan 8 obtained synthetic clinkers that were prepared from oil shale containing up to 5 wt% P 2 O 5 as a secondary component.…”
mentioning
confidence: 99%
“…The use of waste-derived fuels (agricultural crops, animal meat, bone meal) results in increased phosphorus content in cement. It has been shown that phosphorus decomposes or inhibits the formation of alite while stabilising belite and generating free lime (Halicz et al, 1984;Nastac et al, 2007;Nurse, 1952;Stanek and Sulovsky, 2009 On the phase chemistry of Portland cement clinker Hö kfors, Boströ m, Viggh and Backman (Nastac et al, 2007). At concentrations of 0 .…”
Section: Influence Of Phosphorus On Clinker Mineralsmentioning
confidence: 99%
“…With increasing amounts of phosphorus pentoxide in the raw material of clinker, phosphorus was shown to primarily enter the belite phase and to a lesser extent the alite phase (Gutt, 1963;Nastac et al, 2007;Stanek and Sulovsky, 2009). At concentrations above 1% phosphorus pentoxide, a solid solution of phosphorus and belite forms (Nurse, 1952). By examining anhydrous cement (Poulsen et al, 2010) with low concentrations of phosphorus, the element was incorporated in alite and belite phases.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there must be other phenomena as well, along with above mentioned reason, which cause the 138% increase in free lime content at 7 t/hr MBM feeding. It has been shown [7], [23]- [27] that a high level of phosphorous stabilizes belite and hence inhibits the reaction between CaO and belite to form alite. Due to this reason the free lime content can be increased.…”
Section: Mbm Feed Rate(t/hr)mentioning
confidence: 99%